Sosialisasi Pentingnya Menerapkan Airmanship di Perusahaan Pengiriman Barang, PT Halim Mitra Dirgantara (HTC) - Sudarto; Sujono; Potler Gultom; Supri Abu; Bambang Widarto; Nurman Siddiq; Ronny Wazier; Rizky Karo Karo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
The Community Service (PKM) activity organized by the Faculty of Law, Dirgantara Marsekal Suryadarma University, focusing on airmanship socialization at PT Halim Mitra Dirgantara, has provided a comprehensive understanding to all staff regarding the importance of implementing flight safety principles in every task. The PKM methodology was carried out through socialization, legal counseling, and continued with a question and answer session with PT Halim Mitra Dirgantara staff. Airmanship is not only limited to checking and supervision, but also includes a deep understanding of the prevailing laws and regulations in Indonesia. Thus, the company's business activities can run in accordance with established safety rules, thereby increasing public trust and maintaining the Company's reputation.